Isotherms describing physical adsorption of Cr(VI) from aqueous solution using various agricultural wastes as adsorbents. Issue 1 (31st December 2016) - Sharma, Pushpendra Kumar; Ayub, Sohail; Tripathi, Chandra Nath
Abstract: Various agricultural wastes such as peels of pea ( Pisum sativum ) pod, tea ( Camellia sinensis ), and ginger ( Zingiber officinale ) and banana ( Musa lacatan ) waste were used to adsorb Cr(VI) from the aqueous solutions. A comparative adsorption efficiency study for all these adsorbents was done in laboratory for various pH, adsorbent doses, initial chromium concentrations, contact time, adsorbent sizes, temperature, and mixing speeds up to the optimization. The equilibrium sorption data were fitted into Langmuir, Freundlich, and Temkin isotherms and also the various thermodynamic parameters were determined. The value of R 2 was determined for Freundlich, Langmuir, and Temkin as 0.964, 0.963, and 0.858 (pea pod peels waste (PPP)), 0.969, 0.986, and 0.841(tea & ginger waste (T&G)), 0.985, 0.982, and 0.886 (banana peel waste (BW)). The maximum monolayer coverage ( Q 0 ) from Langmuir isotherm model for pea pod, tea & ginger and banana peels waste were found to be 4.33 mg/g, 7.29 mg/g, and 10 mg/g, respectively, with separation factors ( R L ) 0.0331, 0.0343, and 0.0756 which are well within favorable sorption. From Freundlich isotherm model, the sorption intensity ( n ) for the same adsorbents was also less than unity showing normal sorption. The heat of sorption ( B ) was also determined from Temkin isotherm model as 0.215, 0.271, and 0.271, respectively, vividly proving a favorable physical sorption. The Gibbs free energy was found maximum for BW as 6.0679 joule/mole. Out of the above said combination, BW was found the best low-cost adsorbent with high potential for the removal of hexavalent chromium from aqueous solutions.